ANALISIS PENGARUH KUALITAS PRODUK, HARGA DAN KUALITAS PELAYANAN TERHADAP MINAT BELI (STUDI PADA PERCETAKAN FELL OFFSET) - Joko Setiyono; Siti Almaidah (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
Knowing how product quality, product price, and service quality affect consumer interest in buying from Fell Offset printing is the purpose of this study. The population of the study is printing clients from purchases during a three-month period. There are 60 respondents in the research sample with accidental sampling techniques. A number of tests, including testing research instruments and testing classical assumptions were carried out before the data was processed using the SPSS 24.0 application for Windows. Model Y = 7.934 - 0.195 X1 + 0.239 X2 + 0.693X3 e was generated using Multiple Linear Regression analysis techniques. Quality, price, and service quality are known to contribute significantly to the percentage of consumers interested in making a purchase, and the findings of the analysis support the realism of the study model. The independent variable explains 64.6% of the dependent variable, other factors affect 36.4%.